1.introduce a constant k hence
y=kx then find the value of the constant first -4=k2 hence k =-2
y=-2×-6
y=12
Step-by-step explanation:
follow the same procedure for the others and remember if it is inversely proportional then it becomes y=k/x
Answer:
24a+6=12a
Step-by-step explanation:
6(4a+1)
24a+6
2a X 6= 12a
24a+6=12a
Answer:
2
Step-by-step explanation:
you divide the number of dollars he spent by how many pounds of feed he bought to get the dollar/pound rate
Answer:
-1
Step-by-step explanation:
sub in the values of x, y and z into the equation
you get:
(-3)(-4)/(-2)(6)
= 12/-12
= -1
Answer:
6 1/12
Step-by-step explanation:
you would add all the lengths together and then you would have your answer which is 6 1/12